Analisis Kriminologis Tentang Kekerasan Seksual Terhadap Anak di Wilayah Hukum Jakarta Selatan - Untung Sumarwan; p Nugrahadi (Universitas Budi Luhur, 2017)
This study aims to find out about Sexual Violence Against Children in South Jakarta legal area. By using the theory of delinquency and opportunity of Richard A. Cloward and Lloyd E. Ohlin (1960) that the emergence of crime and forms of behavior depends on opportunity, both opportunities to obey the norms, as well as opportunities to deviate norms and the theory of opportunity crime from Clarke & Felson (2011) who views as a situation that can turn into a crime that can benefit the perpetrator, so it can be called Situational Opportunity Crime. This study looks at how occurrences of crime are affected by the physical environment and the environment. To find the data the researchers conducted field observations by visiting the Metro Police Resort South Jakarta and the Komisi Perlindungan Anak Indonesia. The researcher also interviewed one of the staff of the Women and Child Protection Unit Metro Police Resort South Jakarta and the Head of the Secretariat of the Komisi Perlindungan Anak Indonesia. This study has addressed the issue raised that the appearance of crime and its forms of behavior depend on opportunity, both opportunities to obey the prevailing norms, as well as the opportunity to devise norms.